Data organization and preservation in the context of digital and networked media: public’s attitudes, habits and practices in relation to digital curation of personal digital data (Libellarium: journal for research in the field of information and related sciences, 2017)
This paper presents the results of a small scale survey on attitudes, habits and practices of Croatian working population in relation to digital curation of personal digital data. The survey was driven by the following research questions: What are the attitudes of working population towards organizing and safekeeping digital documents that they create in everyday life? To what extent is personal digital archiving among working population a planned activity or just a side-effect of generating content in the digital environment? How do they organize and preserve digital data and documents, both offline and online? What are their attitudes to digital afterlife and digital legacy? Data has been collected in the period from November 2015 to January 2016 through an online questionnaire distributed through online social networks and e-mails aiming to reach the employed population in the age group from 18 to 65 in Croatia. The analysis of the results shows detailed behaviour patterns when it comes to preservation practices as well as attitudes towards taking responsibility for safekeeping personal digital data and documents. The results are also discussed in the light of the implication that these issues may have on user studies and services in libraries and archives.
Keywords: personal digital archiving; data organization; preservation; digital curation